2018
DOI: 10.1111/phen.12240
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic clustering of wingbeat frequency and flight‐associated morphometrics across insect orders

Abstract: Wingbeat frequency in insects is an important variable in aerodynamic and energetic analyses of insect flight and often is studied on a family-or species-level basis. Meta-analyses of these studies report order-level patterns suggesting that flight strategy is moderately well conserved phylogenetically. Studies incorporated into these meta-analyses, however, use variable methodologies across different temperatures, which may confound results and phylogenetic patterns. In the present study, a high-speed camera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 52 publications
(59 reference statements)
2
33
0
Order By: Relevance
“…One possible explanation is that generating sonication frequencies that approach or exceed double that of flight frequencies entails greater physiological costs for smaller bees. To our knowledge, the energetics of floral sonication behavior has not been evaluated, but studies examining the energetics of insect flight have shown that smaller individuals have higher flight frequencies and expend greater energy when flying (or hovering) than larger bodied insects (Casey et al, ; Ellington, ; Tercel, Veronesi, & Pope, ). Thus, for a smaller bee, trying to raise sonication frequency significantly above an already high flight frequency may be energetically more difficult than it is for a larger bee that is starting off at a much lower flight frequency.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that generating sonication frequencies that approach or exceed double that of flight frequencies entails greater physiological costs for smaller bees. To our knowledge, the energetics of floral sonication behavior has not been evaluated, but studies examining the energetics of insect flight have shown that smaller individuals have higher flight frequencies and expend greater energy when flying (or hovering) than larger bodied insects (Casey et al, ; Ellington, ; Tercel, Veronesi, & Pope, ). Thus, for a smaller bee, trying to raise sonication frequency significantly above an already high flight frequency may be energetically more difficult than it is for a larger bee that is starting off at a much lower flight frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Chazot et al ., ; Penz & Heine, ). Estimating the influence of morphological variation among species on flight performance is challenging, particularly because of interactions with other traits that also diverge among species (but see Tercel, Veronesi & Pope, ). By contrast, studies conducted at the population level have allowed demonstrations of how flight performance relates to behaviour and fitness [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Physical characteristics including individual mass, wing area, and wingspan are known to impact wingbeat frequencies in flight 38 . For example, flight-associated morphometrics across insect orders suggest that larger insects may not afford lower wing loadings for their body mass, consequently, leading to increased wingbeat frequency comparing to the group with a similar wing length 39 . Also, individual variation in wing length and area is a function of numerous allometric traits including life history (e.g., the availability of nutritional resources during the larval stage), genetics, and physiology 40 42 .…”
Section: Discussionmentioning
confidence: 99%